Reading philosophy, writing poetry : intertextual modes of making meaning in early medieval China - Swartz, Wendy, 1972- (Published by the Harvard University Asia Center, 2018)
""In a formative period of Chinese culture, early medieval writers made extensive use of a diverse set of resources, in which such major philosophical classics as Laozi, Zhuangzi, and Classic of Changes featured prominently. Reading Philosophy, Writing Poetry examines how these writers understood and manipulated a shared intellectual lexicon to produce meaning. Focusing on works by some of the most important and innovative poets of.
Keywords: Chinese poetry -- 220-589 -- History and criticism.; Chinese literature -- Philosophy.; Intertextuality.; Poésie chinoise -- 220-589 -- Histoire et critique.; Littérature chinoise -- Philosophie.; Intertextualité.; Chinese literature -- Philosophy; Chinese poetry; Intertextuality; 220-589; Criticism, interpretation, etc.